The Relationship between Nurse Therapeutic Communication and Patient Satisfaction in the Inpatient Room of Saint Elisabeth Hospital Medan 2022: Hubungan Komunikasi Terapeutik Perawat dengan Kepuasan Pasien di Ruang Rawat Inap Rumah Sakit Santa Elisabeth Medan Tahun 2022 - MARBUN, GERI GONZALES; Simanullang, Murni Sari Dewi; Ginting, Amnita Anda Yanti (International Journal on Health and Medical Sciences, 2024)
Patient satisfaction is a feeling that arises from the patient as a result of the performance of health services after the patient compares with what he expects. Therapeutic communication is the ability of a nurse to help deal with stress and overcome psychological disorders of patients by providing understanding to reduce the burden on the patient's mind. The purpose of this study was to determine the relationship between nurse therapeutic communication and patient satisfaction in the inpatient room at Saint Elisabeth Hospital Medan. The method used in this research is descriptive correlation with a cross sectional approach. The sampling technique uses is accidental sampling, with a sample of 52 people. The research instrument used is a nurse therapeutic communication questionnaire and a patient satisfaction questionnaire. The results show that the majority of nurses' therapeutic communication with inpatients was good (92.3%), while the satisfaction of inpatients is mostly satisfied (65.4%). statistical test Spearman rank obtained p value = 0.010 where p <0.05, r = 0.354 indicates that there is a moderate relationship between nurse therapeutic communication and inpatient satisfaction at Saint Elisabeth Hospital Medan. Nurses are advised to maintain therapeutic communication in hospitalized patients.